Seed Traits Variation within the Plant in Hyptis suaveolens (L.) Poit - SANTIMOHAN MANDAL,; RABINDRANATH BHATTACHARYYA, (Seed Research, 2026)
The theory of resource allocation has been widely used to examine the physiological basis for variation in reproductive output and the evolution of life history strategies in plant. The variation in numbers of fruit set, seed number, seed size, seed mass and seed germination was investigated at different branch position in Hyptis suaveolens (L) Poit. Significant differences were observed in seed size and seed mass among different branches. Both large and small seeds developed within the same plant. The mass of large seeds were more or less two-fold greater than small seeds. Larger seeds showed a higher germination potential than smaller seeds.